ANALISIS STRATEGI INOVATIF UNTUK MENARIK MINAT GENERASI Z DALAM PRODUKSI BATIK MELALUI PENDEKATAN ERA DIGITAL - Fadali Rahman; Rani Nur Fitrianti; Arikatul Faradies; Amanatus Sholehah; Ach Mahfudz (Jurnal Riset Multidisiplin Edukasi, 2025)
The Indonesian batik industry faces significant challenges in attracting Generation Z, who tend to prefer modern, digital-based fashion products. To overcome this challenge, an innovative marketing strategy is needed by leveraging digital technologies such as augmented reality (AR), virtual reality (VR), and product personalization through digital platforms. This study analyzes how the application of digital technology can enhance the engagement of young consumers in shopping for batik. The results show that the use of AR and VR can create a more immersive and interactive shopping experience, while product personalization through digital platforms increases consumer satisfaction. By integrating these elements into marketing strategies, batik can be positioned as a fashion product relevant to Generation Z's lifestyle and have global appeal.